ANALYSIS KARATE TECHNIQUE SKILL WOMEN KUMITE IN SEA GAMES 2017 - Azizah, Arbaatin Nur (Jurnal Kesehatan Olahraga, 2019)
Karate is a sport of martial arts originating from Japan, according to Ivan (2012: 20) karate comes from twowords kanji"kara" meaning empty "te" means hand, so karate is called empty-handed exercise. Karate is an achievement sport that is able to bring the name of the Indonesian people to the world level. One of the achievements in the championship of sea ??games in 2017 is the karate sport in thenumber of the kumite daughter, Srunita Sari Sukatendel and Cok Istri Agung Sanistyarani who managed to bring gold to Indonesia. Therefore, the researcher conducted a research with the title Analysis of Competing Technical Skills of Karate Sports Branch Number of Kumite Putri at Sea Games 2017 in Malaysia. The purpose of this study was to determine the most dominant technical skills displayed in thenumber match kumite of karate sports. The type of research used in the research this is a Non-Experiment with qualitative descriptive analysis research method with data retrieval in the form of observation. Here are the results of amatch kumite individual senior princess in percentage form, namely: 1) techniques tsuki gyaku 30.84%, 2) techniques, geri MAWASHI 30.84%                3) engineering oi tsuki 18.79%, 4) engineering ushiro geri 10 , 52%, 5)technique ren tsuki 5.26%, 6) harai 3.00% technique, 7)technique geri ura mawashi 0.75%. These results are obtained by using the percentage formula that is, % =? 100%. It can be concluded that the technique gyaku tsuki and geri MAWASHI is the dominant technique used in the final round ofnumbers kumite women'swith the percentage 30.84% .Inmatch kumite the sport karateat the championships sea games2017attack techniques  gyakutsuki and geri MAWASHI more effective againstgain pointand dominant use of theclass is kumite -50 kg and +68 kg. Keywords: Karate, Technique, Competence Skills